Pengaruh Budaya Organisasi, Pelatihan Kerja dan Kompensasi terhadap Retensi Karyawan di PT. Karya Safari di Denpasar - Rika Gayatri, Ni Putu Diah; Yudy Wijaya, Putu; Sri Hartati, Putu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
This research was conducted with the aim of knowing the influence of organizational culture, training and compensation on employee retention at PT. Safari Works. The population of this study is the number of employees at PT Karya Safari, namely 32 people with a total sample of 32 respondents who are determined by the saturation sample determination method. The data in this study were obtained through the results of distributing questionnaires which were later analyzed using multiple linear regression analysis techniques. Based on the results of the study it can be seen that: Organizational culture has a positive and significant effect on employee retention. Job training has a positive and significant effect on employee retention. Compensation has a positive and significant effect on employee retention. Organizational Culture, Job Training and Compensation have a positive and significant effect on employee retention. Looking at the research results, PT. Karya Safari must prepare SOPs related to communication procedures in the work environment so that polite, directed, and clear communication will be formed between employees